An ecosystem approach to human health and the prevention of cutaneous leishmaniasis in Tumaco, Colombia - Rojas Carlos A. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
A study was conducted during 1996-1997 in 20 villages of Tumaco, Colombia, to evaluate the effectiveness of personal protective measures against cutaneous leishmaniasis (CL). The intervention was effective, but the high costs of the preventive measures and the lack of a more holistic approach hampered the intervention's sustainability. This paper analyzes the results using an ecosystem approach to human health. Using this approach, we found that CL has been present in the study area for a long time and affects farmers and those living closest to the forest. The forest constitutes the habitat for insect vectors (sandflies) and parasite reservoirs (wild mammals). Four spatial scales were identified in this ecosystem: residential, village, regional, and global. From the ecosystem perspective, three interventions are proposed to prevent CL in the 20 villages: improve housing construction, organize village housing in clusters, and make diagnosis and treatment of CL more accessible. The design and implementation of these interventions require active involvement by people with the disease (village inhabitants) and decision-makers (local authorities).